Tunggu Tubang and Ulu Ayek: Social Mechanism of Sustainable Protected Forest Management - Edwin Martin; Didik Suharjito; Dudung Darusman; Satyawan Sunito; Bondan Winarno (Institut Pertanian Bogor (IPB University), 2016)
Practices and traditional knowledge of smallholder farmers living forests is a potential resource to enhance landscape management. However, knowledge of the smallholder-forest relationship is still rare to explore social mechanisms that allow their relationship lasting long. The research aims to obtain further understanding of the traditional practices of forest management in Semende, South Sumatera. We visited 32 villages in Semende and stayed on several occasions in the 10 villages. We used descriptive phenomenological approach to understand the social process of successful forest management by farmers. We find the key that leads to the relations of sawah-forest to be able to be maintained against changes, that is consistent attitude towards the core values of life, whatever happens and changes. Social mechanism in the form of practices of knowledge-institution-tunggu tubang is an integral package to ensure the sustainability of forest. The social mechanism is driven by the values of respect for the elderly, extended family, real work, the search for stability and serenity in the bonds of humanity. These findings may be valuable lessons for improving forest policy.